“The Most Unsettling Reality is Our Own”: Instability of Form After the Global Turn - Gush, Rose-Anne (The Nordic Journal of Aesthetics, 2025)
This article takes historical surrealist works to explore what I term “instability of form.” Focusing on the poetic works of Suzanne Césaire published in Tropiques during the 1940s and the 1953 surrealist film Statues Also Die (Les statues meurent aussi) by Chris Marker, Alain Resnais, and Ghislain Cloquet, it situates this inquiry within the turn to theories of “global art” and their political aesthetics. The hypothesis is that literature on “global art” has neglected to investigate the “form” of anti- or a-formal artworks. Critical assessments have privileged sociological, geopolitical or content based readings, neglecting to mediate analyses of geopolitical transformations through analyses of art’s formal innovations. In response, the article proposes a dual theoretical framework to reinterpret these works. First, it employs Theodor W. Adorno’s perspicacious concept of “Verfransung” the fraying of the boundaries between the art genres, explicated in “Art and the Arts” (1967), arguing for its relevance for resituating “global art” in the present. Second, it uses the Warwick Research Collective’s (WReC) model of “combined and uneven development” to understand these practices as formed by a dialectic of core/periphery relations of the capitalist world-system. Through this framework, the article explores how formal instability relates to artistic intimations of catastrophe and crisis, to art’s articulation of the continuities between colonialism, fascism and capitalism. By interpreting how these surrealist works index the uneven temporalities and violent hierarchies of global modernity—for example, through methods of “telescoping,”—the article demonstrates modes of political aesthetics that attempt to corrode the naturalised categories of racialisation, genre, and value. It argues that these aesthetic practices point toward an unfinished project of liberation, one that requires embracing art’s capacity for boundary violation, in ways that have contributed and might still contribute to forms of anti-fascist and anti-colonial resistance.